(untitled) (Ames, Iowa, USA, 1997)
The book provides information on poultry disease. The accelerating pace of knowledge generation dictates the need for continual revision and updating of this universal reference. An expanded and diverse group of experts from around the globe lend their expertise to authorship of the eleventh edition, which contains the latest credible information on the subject.
Keywords: Poultry; Diseases